FC049: Nefecon® (Budesonide) is an Epigenetic Modifier in IGA Nephropathy. (3rd May 2022) - Bhachu, Jasraj; Molyneux, Karen; Barratt, Jonathan; Pawluczyk, Izabella
Abstract: BACKGROUND AND AIMS: In recent years, the dysregulated expression of microRNAs (miRs)—small molecules of noncoding RNA that epigenetically fine-tune post-transcriptional gene expression—has been increasingly implicated in the pathogenesis of IgA nephropathy (IgAN). Extracellular miRs, contained within extracellular vesicles such as exosomes and microvesicles, are thought to function as important intercellular and interorgan modes of communication in health and disease. In the current study, next-generation sequencing (NGS) and subsequent real-time quantitative polymerase chain reaction (RT-qPCR) validation were performed to identify serum miRs associated with a high risk of future kidney function decline in IgAN. We then went on to determine whether treatment with Nefecon ® 16 mg/day for 9 months was capable of modifying the serum levels of miRs associated with high-risk IgAN. This study was supported by a grant from Calliditas Therapeutics AB. METHOD: NGS was performed by Qiagen (Germany) on serum from patients with IgAN (10 at high risk and 10 at low risk of progression) or membranous nephropathy (MN, n =10), as well as healthy individuals (HS, n =10). Sequencing data were validated by RT-qPCR using TaqMan miR PCR assays in independent sets of serum samples (20 per cohort). Using the Total Exosome Isolation (from serum) reagent (Thermo Fisher Scientific, UK), extracellular exosomes were isolated from the serum of participants of the NEFIGAN trial from the placebo group ( n =40) and Nefecon ® 16 mg/day group ( n =40) at the start of treatment (SOT) and end of treatment (EOT). RNA was isolated and levels of miRs-483-5p and -122-5p were measured by RT-qPCR. The NEFIGAN trial (NCT01738035) was a randomized, double-blind, placebo-controlled Phase 2b trial designed to assess the safety and efficacy of Nefecon ® a novel targeted-release formulation of budesonide, designed to deliver the drug to the distal ileum in patients with IgAN. The trial comprised a 6-month run-in, a 9-month treatment and a 3-month follow-up phase. A total of 48 patients received Nefecon ® 16 mg/day, 51 patients received Nefecon ® 8 mg/day and 50 patients received placebo. The key result of the study was that Nefecon ® 16 mg/day, added to optimized renin–angiotensin system blockade, reduced proteinuria and stabilized estimated glomerular filtration rate in patients with IgAN. These findings have now been replicated in the NefIgArd study, which released data in 2021. RESULTS: miRs-483-5p and -122-5p were significantly overexpressed in the serum of patients with IgAN at high risk of progression compared with those who had stable IgAN or HS, but not compared with patients with MN. Both miRs were also found to be significantly increased in extracellular exosomes in high-risk IgAN compared with low-risk IgAN, HS and MN. Interestingly, levels of exosomal miRs-483-5p and -122-5p did not correlate with total serum IgA, IgA1, galactose-deficient IgA1 or IgA–IgG immune complex levels, suggesting a novel mechanism of action. Treatment with 16 mg/day of Nefecon ® led to a significant reduction in the exosomal levels of miR-122-5p, while no change in miR-483-5p levels was observed in the treated group. CONCLUSION: These data reveal a dysregulation of systemic exosomal miR expression in IgAN, and demonstrate for the first time that it is possible to pharmacologically modify the miR content of circulating exosomes in IgAN. Treatment with Nefecon ® 16 mg/day for 9 months selectively downregulated exosomal miR-122-5p, while having no effect on exosomal miR-483-5p levels, arguing against a generalized 'anti-miR' effect of Nefecon ® . Studies are ongoing to both precisely delineate the cellular source(s) of these exosomes and determine the downstream impact of these changes on glomerular and tubulointerstitial biology.